Etične dileme in izzivi humanizma v socialnem delu danes - Sobočan, Ana Marija (Socialno delo, 2021)
Social work is permeated with ethical dilemmas. These also arise from the conflict between humanistic principles and the ethical imperatives of social work with current orientations in social policy and macroeconomic processes. From this point of view, various elements and factors of the neoliberal structure are also relevant for understanding modern social work practices characterized by deregulation, deprofessionalization, privatization, introduction of market principles into services, etc. In this way, social work loses its capacity to analyze and change the systemic, collective and individual conditions that organize and determine our lives. The notion of risk replaces the notion of needs, individual blame replaces the imperative of solidarity, and so on. As the results of research with social workers in Slovenia and foreign literature show, resistance to the demoralizing situation in the profession does exist. Social work needs to resume its advocacy, critical, radical stance, and with the help of critical reflection and other methods defend its mandate for human rights and social justice.
Keywords: corporativism; critical thinking; ethics; etika; korporativizem; kritično mišljenje; neoliberalism; neoliberalizem; risk; socialna država; tveganje; welfare state,